Estrutura de radiologia nos Centros de Especialidades Odontológicas (CEO) do Brasil: avanços e desafios - CAMPOS, Magda Lyce Rodrigues (2022)
Dental radiology (DR) is the specialty that is dedicated to the study and practice of the complementary diagnostic method through image exams of the orofacial region and has the purpose of initial evaluation, control and final evaluation of a treatment. The Unified Health System (SUS, in portuguese) offers DR services mostly in Dental Specialty Centers (CEO, in portuguese). The aim was to analyze the DR services structure available in CEO in Brazil, to identify advances and challenges between 2014 and 2018. This is an ecological study, using data from the external evaluation of the cycles of the Access and Quality Improvement Program-CEO (PMAQ-CEO), Cycle I (c1), in 2014 and Cycle II (c2), in 2018.We included all CEO evaluated at both times (n: 889). Latent class transition analysis was used to identify patterns for CEO structure in relation to DR, latent status (LS). Of the CEO evaluated, the largest number was in the Northeast (n:340, 38.25%). In c1, 20.25% of CEO had a dental radiologist and in c2, 10.35%. 3.82% had a panoramic radiography device, in c1 and in c2, 5.29%. In c1, 47.58% of CEO had an exclusive room for DR and in c2, 51.86%. Most had at least one periapical radiograph, a lead apron with thyroid protector, a câmara obscura, and a negatoscope. The model with 3 SL was used, which were named: (1) Best structure for DR (n:377); (2) Median structure for DR (n: 379) and (3) Worst structure for DR (n:133). The transition analysis of latent classes showed that no CEO belonging to the “better structure” class presented a worsening between 2014 and 2018,4.3% of the median CEO and 16.6% of the worst CEO moved to the best structure status between cycles, while 66.3% of the CEO transitioned from the “worst” SL to the “Medium Structure”. It is concluded that there was an improvement in the structure of dental radiology in CEO in Brazil, except for specialized professionals, pointing to the need to restructure the human resources policy in the SUS.